MENGATUR HAK AKSES PEMAKAI DENGAN FORM HAK AKSES MENGGUNAKAN VISUAL BASIC .NET - khoirur rozikin; nuris setiawan (Elkom : Jurnal Elektronika dan Komputer, 2020)
An application is usually used by several users where each user has access rights to certain forms in accordance with their authority or position. For example, the Inventory application or inventory is used by the Manager to view reports, the Warehouse section to check the stock of goods and the cashier to make purchases and sales transactions. Another example is the Academic Value application used by the Administration to input student and course data, Lecturers to input academic value data and Students to view academic value data. Access rights to use certain forms can be set directly in the program code with the consequence that if there is a change in access rights by certain users, you must change the program code, this is not a problem if the company can still contact the programmer to change the program code according to changes in user access rights but it will be a problem if the program maker cannot be contacted by the company to change the program code according to changes in user access rights.